Hukum Hibah Tanah untuk Gereja Persepektif Empat Mazhab - Miqdarul Khoir Syarofit; Anisatun Nur Laili (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Social media in the current era is the fastest link between humans, various events in the fields of economy, education, and law continue to experience new things that have not even been encountered in the past. Not long ago, there was news that went viral among netizens regarding the giving of land by a Muslim in the Kalimantan area, to the church for restoration purposes. Islam as a religion of rahmatan lil 'alamin, of course, must be swift in giving laws related to new problems that are developing in society. This study uses the library research method, where the researcher focuses on studying the classic books and the sources needed to solve the law on the case. A formulation is obtained that the grant is basically a sunnah, if it has fulfilled the pillars and conditions determined by the Shari'a. One of the requirements for the gift is that the benefit of the object given does not violate religion. In the case of giving land from a Muslim for the construction of a church, according to the majority of scholars, it leads to haram law, because it is included in the category of synergy in disobedience, even disbelief. However, there is an opinion from Imam Abi Hanifah which states that this action is allowed if the location of the land given is in a village inhabited by non-Muslims. injured, the new disobedience occurred after the land given earlier functioned for the construction or restoration of the church